Midwives' Knowledge, Attitudes, and Skills in Screening Maternal Health Postpartum - Pujianti Harahap, Ana; Sakundarno Adi, Mateus; Sriatmi, Ayun; Tri Purnami, Cahya (Mulawarman International Conference on Tropical Public Health, 2025)
Background : Perinatal Mental Health (PMH) is a mental health issue that occurs in pregnant women and postpartum. The care of mental health is greatly influenced by the knowledge, attitudes, and skills of midwives in conducting mental health screenings Objective : Therefore, this study aims to analyze the knowledge, attitudes, and skills of midwives in implementing mental health screenings for postpartum mothers. Research Methods/ Implementation Methods : This research utilized a cross-sectional design that surveyed 102 (one hundred and two) midwives working in postpartum care rooms at healthcare centers in Indonesia. The sampling was conducted using Consecutive Sampling in December 2023, with the criteria of midwives who are actively working and willing to be respondents. Research data were collected electronically using a questionnaire through Google Forms, distributed via WhatsApp using Snowball sampling technique to evaluate the demographic characteristics, knowledge, attitudes, and skills of midwives in conducting postpartum maternal health screenings. Data were analyzed using SPSS version 27 and tested using the Chi-square test with significant at p < 0.05. Results : Among midwives, 51.9% are knowledgeable about PMH screening. Of the 53 midwives surveyed, 80% demonstrated a high level of knowledge, while 98.1% have a positive attitude toward PMH screening. However, only 47.1% presented proficient skills in this area. Statistical analysis reveals a significant correlation between midwives’ knowledge and attitudes regarding PMH screening, with a p-value of 0.001, which is below the threshold of 0.05. Conclusion/Lesson Learned : It is essential to provide training for midwives in the implementation of PMH screening for postpartum mothers to ensure optimal care outcomes.